Earnings management behavior in Malaysia: the role of ownership structure and external auditing / Nor Irdawati Mahyuddin ... [et al.] - Mahyuddin, Nor Irdawati; Mohd Nor, Mohd Nazli; Hashim, Hafiza Aishah; Nahar, Hairul Suhaimi (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
This paper aims to empirically investigate firms' earnings management (EM) behaviour, representing an issue in the realm of corporate financial reporting. Specifically, it explores the strategic roles of two common governance elements of ownership (managerial, institutional and family) and external audit in shaping the firms' EM behaviour based on the two common EM attributes of Discretionary Accruals (DA) and Real Activities EM (REM). The analyses based on 227 survived Malaysian listed firms throughout the sixteen-year period from 2001 to 2016 (3,632 firm-year observations) indicate a dynamic EM behaviour depending on the presence of different ownership structures. Whilst a high percentage of family and institutional ownership mitigates DA, it however does not hold true for REM. Further, this paper also shows that the external control mechanism of audit quality is not significant in mitigating both EM attributes. The empirical results suggest that firms facing different challenges would affect the firms' financial reporting behaviours in their choice of EM. The paper adds to the growing body of empirical knowledge dealing with the determinants of DA and REM from the lens of an emerging economy like Malaysia.